2014
DOI: 10.1002/ejic.201402475
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Multiple Metal–Organic Framework Formation: Concomitant Generation of Structural Isomers or of Drastically Distinct Materials

Abstract: The solvothermal reaction of 2,5‐dihydroxyterephthalic acid (H2dhtp) and magnesium(II) nitrate in N,N‐dimethylformamide (DMF) led to the simultaneous formation of two structural isomers, namely, the lvt network Mg(dhtp)(dmf)2 (1) and the compound Mg3(dhtp)3(dmf)6·0.75H2O (2) with the pcu α‐Po primitive cubic topology. The same reaction conditions with manganese(II) nitrate and terephthalic acid (H2tp) resulted in the concomitant generation of two drastically different metal–organic frameworks (MOFs), namely, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…XXXX, XXX, XXX−XXX (DMF) 2 ] (the latter adopts the sra topology but has mistakenly reported as lvt). 3g, 18 Photophysical Studies. As seen in Figure 7, illumination with a laboratory UV lamp (ca.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XXXX, XXX, XXX−XXX (DMF) 2 ] (the latter adopts the sra topology but has mistakenly reported as lvt). 3g, 18 Photophysical Studies. As seen in Figure 7, illumination with a laboratory UV lamp (ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, AEMOF-3 is the only example of alkaline earth metal ion−H 2 dhtp 2− MOF with a 2-D structure (all other examples display 3D frameworks). Finally, comparing the topological features of AEMOF-2−6 with those of known alkaline earth−H 2 dhtp 2− MOFs it was realized that AEMOFs-2,3 display network topologies not shown by other AEMOFs, whereas AEMOF-5 adopts the same topology with the compound [Mg 3 (H 2 dhtp) 3 (DMF) 6 ]·0.75H 2 O,18 and AEMOF-4,6 adopt the same topology with [Mg(H 2 dhtp)-…”
mentioning
confidence: 97%
“…A search of the Cambridge Crystallographic Data Centre reveals 5 different coordination polymers derived from magnesium and the di-anion of 2,5-dihydroxyterephthalate, in addition to the aforementioned CPO-26-Mg and CPO-27-Mg, all of which contain a three-dimensional coordination framework. One was prepared from DMF, [26] one from DMF in the presence of NEt 3 , [27] and one from aqueous DMA, [28] whilst the remaining two were prepared from DMA or aqueous N-methyl pyrrolidone. [29] This is the first example of a material prepared from a predominately aqueous solution.…”
Section: Crystallographymentioning
confidence: 99%
“…It turns out that the topology observed for the Cd-MOF is heretofore unprecedented. The formation of two different types of MOFs with different compositions concomitantly in the same reaction vessel is a rare occurrence. As mentioned earlier, the reaction of H 4 L with Zn­(II) salt at 90 °C gives rise to two different forms, referred to as Zn-Lsqc and Zn-Ldia . Quite remarkably, temperature dependence of the formation of concomitant MOFs revealed that one observes the formation of Zn-Ldia exclusively at 110 °C, which suggests that the latter corresponds to the thermodynamic form of the two MOFs.…”
Section: Resultsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are exotic porous materials that permit diverse applications such as gas storage, molecular sieving, sensing, magnetism, catalysis, bioimaging, drug delivery, etc. Synthesis of MOFs with predefined framework structures remains still a challenge, as the reactions to access them depend on a variety of parameters, which include metal–linker ratio, pH, solvent employed, temperature, coordination number and geometry of the metal ion, nature of the counterion used, additive, etc. It is needless to say that the structural attributes of an organic linker play a crucial role in determining the structures as well as topologies of the derived frameworks due to variable coordination modes, conformational flexibility, and presence of different secondary functional groups. , The synthesis/crystallization process by which the MOFs are accessed is sensitive to different reaction parameters, and often results in the occurrence of unusual secondary building units (SBUs). , The latter in turn lead to formation of interesting and varied network structures. Consequently, formation of two or more different metal–organic frameworks from the same synthesis/crystallization pot with intriguing structure types is not rare, which indeed subverts the anticipated framework structures based on connectivity dispositions of the linker and coordination preferences of the metal ions. In principle, one may access coordination polymers with the same framework chemical formula, but different structures or those that differ in terms of both chemical formula as well as structural attributes. The former have been popularly termed “supramolecular isomers”, , while those differing in chemical formulas have been termed “structural isomers”. , The literature reveals abundant examples of solvent-, template-, counterion-, additive-, and temperature-dependent formation of isomeric coordination polymers. , MOFs being materials whose structures and chemical functionalities can be tuned in a bottom-up approach through the linkers modifications, the structure–property relationships help in deciphering subtle factors that are important for their functional properties.…”
Section: Introductionmentioning
confidence: 99%